Mobile bystanders and rubbernecks, disaster tourists, and helpers. Towards a theoretical framework for critically studying action possibilities at accident sites. (September 2021) - Andersson, Linus; Sundin, Ebba
This article addresses the phenomenon of mobile bystanders who use their smartphones to film or take photographs at accident scenes, instead of offering their help to people in need or to assist medical units. This phenomenon has been extensively discussed in Swedish news media in recent years since it has been described as a growing problem for first responders, such as paramedics, police, and firefighters. This article aims to identify theoretical perspectives that are relevant for analyzing mobile media practices and discuss the ethical implications of these perspectives. Our purpose is twofold: we want to develop a theoretical framework for critically approaching mobile media practices, and we want to contribute to discussions concerning well-being in a time marked by mediatization and digitalization. In this pursuit, we combine theory from social psychology about how people behave at traumatic scenes with discussions about witnessing in and through media, as developed in media and communication studies. Both perspectives offer various implications for normative inquiry, and in our discussion, we argue that mobile bystanders must be considered simultaneously as transgressors of social norms and as emphatic witnesses behaving in accordance with the digital media age. The article ends with a discussion regarding the implications for further research.